Pengeluaran Tahanan Demi Hukum Yang Telah Habis Masa Penahanan Guna Mengurangi Fenomena Overcrowding di Rutan Kelas I Depok - Winanto, Wahyu Andika; Hendrawarman (PT Elaborium Elevasi Indonesia, 2025)
This research is motivated by the problem of overcrowding in the State Detention Center (Rutan) or Correctional Institution (Lapas). Overcrowding itself is an event where the accumulation of a number of detainees living in the detention center exceeds the capacity, as happened in the Depok class I detention center. The overcrowded phenomenon can certainly lead to the non-fulfillment of the rights of detainees that should be guaranteed while in the detention facility or prison. This research aims to find out the causal factors and the impact of the overcrowding phenomenon in the Class I Depok Detention Center and to find out whether Expulsion by law based on Minister of Law and Human Rights Regulation No. M.HH-24.PK.01.01.01 of 2011 can be an alternative to solve the problem of overcrowding in detention centers. The research found that the legal process is considered slow in handling a case and the lack of capacity of detention centers and law enforcers, in this case the capacity of prison guards, is a factor causing overcrowding in the Depok class I detention center, which can have a negative impact on detainee supervision and prison care and also violate the rights of detainees. Regulation of the Minister of Law and Human Rights No. M.HH-24.PK.01.01.01 of 2011 concerning the Release of Detainees by Law, which explains that detainees must be released if the detention period has expired by law. By releasing prisoners who have expired their detention period, it will certainly be able to prevent overcrowding and overstaying in detention centers and prisons. The release of detainees by law in this case can be said to be effective in solving the problem of the overcrowding phenomenon in the Depok Class I Detention Center.